Sorafenib enriches epithelial cell adhesion molecule–positive tumor initiating cells and exacerbates a subtype of hepatocellular carcinoma through TSC2‐AKT cascade. Issue 6 (24th October 2015) - Guan, Dong‐Xian; Shi, Jie; Zhang, Yang; Zhao, Jiang‐Sha; Long, Ling‐Yun; Chen, Tian‐Wei; Zhang, Er‐Bin; Feng, Yuan‐Yuan; Bao, Wen‐Dai; Deng, Yue‐Zhen; Qiu, Lin; Zhang, Xue‐Li; et al.
Abstract : Sorafenib is a specific adenosine triphosphate–competitive RAF inhibitor used as a first‐line treatment of advanced hepatocellular carcinoma (HCC). However, the responses are variable, reflecting heterogeneity of the disease, while the resistance mechanism remains poorly understood. Here, we report that sorafenib treatment can exacerbate disease progression in both patient‐derived xenografts and cell line–derived xenografts and that the therapeutic effect of the drug inversely covaries to the ratio of epithelial cell adhesion molecule–positive cells, which may be tumor initiating cells in HCC. The TSC2‐AKT cascade mediates this sorafenib resistance. In response to sorafenib treatment, formation of the TSC1/2 complex is enhanced, causing increased phosphorylation of AKT, which contributes to up‐regulation of "stemness"‐related genes in epithelial cell adhesion molecule–positive cells and enhancement of tumorigenicity. The expression of TSC2 negatively correlated with prognosis in clinical sorafenib therapy. Furthermore, all‐ trans retinoic acid decreased AKT activity, reduced the epithelial cell adhesion molecule–positive cell population enriched by sorafenib, and potentiated the therapeutic effect of sorafenib in the patient‐derived xenograft model. Conclusion : Our findings suggest that a subtype of HCC is not suitable for sorafenib therapy; this resistance to sorafenib can be predicted by the status of TSC2, and agents inducing differentiation of tumor initiating cells (e.g., all‐ trans retinoic acid) should improve the prognosis of this subtype of HCC.(Hepatology 2015;62:1791–1803)